THE INFLUENCE OF PERSONALITY FACTORS ON INVESTMENT DECISIONS WITH INVESTMENT INTENTION AS A MEDIATING VARIABLE (AN EMPIRICAL STUDY IN INDONESIA) - Siti Hardiyanti; Wendy Wendy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of personality factors consisting of Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism on Investment Decisions with Investment Intention as an intervening variable among investors in Indonesia. The study employs a quantitative approach with a causal associative design. The research population consists of investors in Indonesia, with a sample of 487 respondents determined through purposive sampling. Primary data were collected through questionnaires, while secondary data were obtained from official publications related to the development of investors in Indonesia. Data analysis was conducted using SEM-PLS with SmartPLS through the evaluation of the outer model (convergent validity, discriminant validity, AVE, reliability, and collinearity) and the inner model (R-square and hypothesis testing through bootstrapping). The results indicate that all constructs meet the criteria of validity and reliability. The model demonstrates moderate explanatory power with an R² value of investment intention of 0.577 and an R² value of investment decisions of 0.651. Structurally, Openness, Conscientiousness, Extraversion, and Agreeableness have a significant positive effect on Investment Intention and Investment Decisions, while Neuroticism does not have a significant effect on either. Investment Intention has a significant positive effect on Investment Decisions and acts as a partial mediator in the relationship between Openness, Conscientiousness, Extraversion, and Agreeableness on Investment Decisions, but does not mediate the effect of Neuroticism.